Pengaruh Pendidikan, Pelatihan, Disiplin dan Kompensasi Terhadap Prestasi Kerja Karyawan Rumah Sakit Umum Salewangang Di Kabupaten Maros - Kadir Tangdiesak (Journal of Management Science (JMS), 2020)
The aims of this research are : (1) to analyse the influence of education variable to make-up of labour capacity of officer at home public pain ofsalewangang of regency Maros. (2) to analyse the influence of training variable to make-up of labour capacity at home common public pain ofsalewangang of regency Maros. (3) to analyse the influence of discipline variable to make-up of labour capacity at home commo public pain ofsalewangang of regency Maros. (4) to analyse the influence of compensation variable to make-up of labour capacity at home common public pain of salewangang of regency Maros. Research conducted with the observation method, kuesioner, interview and survey of through passing 66 responder selected by as sampel. Analyzer used by is descriptive analysis and statistical analysis by mengunakan is doubled regresi liner. Result of this research indicate that pursuant to result of processing of regresi liner of above showing fourth of variable that is education, training of discipline and compensation, having an effect on positive to labour capacity common public hospital officer of Salewangang of Regency Maros. And most dominant have an effect on to labour capacity of officer is discipline.Suggested that by a the variable above is ever paid attention to by simultan and kontinyu of so that be discipline mount which in the end, having an effect on by signifikan to make-up of labour capacity officer.